Low-risk lifestyle and health factors and risk of mortality and vascular complications in Chinese patients with diabetes - Sun, Z; Hu, Y; Yu, C; Guo, Y; Pang, Y; Sun, D; Pei, P; Yang, L; Chen, Y; Du, H; Jin, J; Burgess, S; et al. (Oxford University Press, 2022)
Background There is an evidence gap about whether a low-risk lifestyle is as important as achieving blood pressure (BP) and random blood glucose (RBG) control.